Analisis Nilai Peduli Sosial Film Animasi Adit dan Sopo Jarwo untuk Siswa Sekolah Dasar - Sinta Febriana; Arya Setya Nugroho (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The low sense of social concern can be seen from the fact that there are still students who do not want to help their friends when they are having difficulties, the lack of a sense of greeting between students and indifference to others. This study aimed to analyze the social care value of the animated film Adit and Sopo Jarwo for elementary school students. The method in this research is qualitative with a descriptive approach. Data collection was done by observation and documentation. The instrument in this study was the observation sheet. The data were analyzed by content analysis, namely describing the value of social care in the animated film Adit and Sopo Jarwo. The research resulted from the 3 episodes that have been analyzed in the animated film Adit and Sopo Jarwo obtained 13 attitudes that show social concern. Various groups can watch Adit and Sopo Jarwo's animated film because this film contains the educational value which can later be applied in everyday life.